Unveiling the Impact of Good Corporate Governance and Temporary Shirkah Funds on Maqashid Shariah Performance - Dwianto, Agus; Qurrota A'yun, Annisa; Hardina, Lulu; Arum, Nurlita; Karmila, Yusri (Journal International Economic Sharia, 2024)
This study investigates the influence of Good Corporate Governance (GCG) and Temporary Shirkah Fund (TSF) on the performance of Maqashid Shariah in Islamic banks in Indonesia from 2018 to 2023. Using secondary data analysis, the study employs regression analysis to test the hypotheses. The findings reveal that neither Good Corporate Governance nor TSF significantly affects the performance of Maqashid Shariah during the study period. These results are consistent with previous research indicating a lack of significant impact Good Corporate Governance and TSF on Maqashid Shariah performance in Islamic banks. The discussion suggests that the implementation of Good corporate governance may not directly translate into improved Maqashid Shariah performance due to potential misalignment between governance practices and Shariah principles. Moreover, the study highlights the importance of further research and enhanced implementation of Good Corporate Governance and TSF practices to promote the achievement of Maqashid Shariah objectives in Islamic banking institutions. This research contributes to the ongoing discourse on corporate governance and Shariah compliance in Islamic finance and provides insights for policymakers, regulators, and practitioners aiming to strengthen governance frameworks and enhance Shariah-based performance in Islamic banks